PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA - Reka Dina; Said Musnadi (Departemen Manajemen, 2020)
This study to aims to examine the effect of ownership structure on dividend policy in non-financial companies in Indonesia Stock Exchange on period 2011-2017. The technique used in this study is purposive sampling based on some certain criterias to obtain 26 samples from companies. The Fixed Effect Model method is used for the analysis. The results show that institutional ownership has significant positive effects on dividend policy. The higher institutional ownership, the greater monitoring of institutional to management, so the shareholders will get more profit of dividend. Meanwhile managerial ownership has significant negative effects on dividend policy. The higher managerial ownership makes companies more likely to allocate profit to retained earning and the lower managerial ownership, the company will pay more dividend as a good sign for future corporate performance.Keywords: Agency theory, institutional ownership, managerial ownership and dividend policy.